Peranangan Pusat Kreativitas Anak dengan Pendekatan Arsitektur Perilaku di Kota Gorontalo - Isrami Putri; Lydia Surijani Tatura; Abdi Gunawan Djafar (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
Creativity is an essential ability for generating new ideas and solving problems, particularly for children aged 4-12 who are in a period of rapid development. In Gorontalo City, many children in this age range face psychological barriers such as a lack of self-confidence and initiative, compounded by limited parental attention to developing their interests and talents. Consequently, their creative potential is often stunted. This research aims to design a children's creativity center to provide a supportive and imagination-stimulating environment. This facility will offer various media for expression, including art, music, and interactive games, to encourage children to explore their potential actively. The design methodology involves site analysis to establish effective zoning and applies the concept of Behavioral Architecture. This approach ensures that each space is tailored to the behavioral patterns and psychological needs of children, optimizing their interaction with the environment. The final output is a functional design for a creativity center, intended to help children develop their potential and grow into more self-confident individuals.